Uwarunkowania rywalizacji politycznej Platformy Obywatelskiej RP i Prawa i Sprawiedliwości - Maj, Przemysław (Polityka i Społeczeństwo, 2021)
The author presented the determinants of rivalry between PO and PiS. The analysis covered the genesis of both parties, existing and new socio-political divisions created by the parties; party memberships; differences in strategy and paradigms, and the differences of party programmes.